Public Policy Dynamics in the Era of Globalization - Adila, Wafa (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The dynamics of public policy in the era of globalization, focusing on how globalization affects policies across various sectors such as economy, social issues, culture, and security. The study identifies the challenges and opportunities posed by globalization and examines how countries, particularly Indonesia, are adapting through policies such as the Omnibus Law and the Merdeka Curriculum. Theories of globalization, including modernization, dependency, and world-systems, are used to understand policy changes. Key findings include recommendations for strengthening economic regulation, enhancing educational quality, preserving culture, and reinforcing international security cooperation. Further research is suggested to evaluate the impact of globalization on inequality, policy effectiveness, the role of the private sector and civil society, and environmental policies for more effective and sustainable policy strategies. This research employs a descriptive qualitative method to analyze the dynamics of public policy in the era of globalization.